Behind the adolescent filter: Unveiling the connection between digital body image edition, satisfaction and well-being - Vizcaíno-Verdú, Arantxa; Feijoo, Beatriz; Sádaba, Charo (Atlantic Journal of Communication, 2025)
Behind the adolescent filter lies a complex relationship between digital tools used to alter appearance and their impact on body satisfaction and well-being. This study quantitatively examined the association between these factors in 1,082 Spanish adolescents aged 12 to 17, focusing on gender and age differences. Non-parametric tests revealed significant gender disparities, with girls using filters more frequently to modify facial features and body shape. Older adolescents (15–17 years) also had higher filter usage than younger participants. Correlational analyses revealed weak but significant negative links between frequent filter use and overall body satisfaction. Regression analyses indicated that modifying facial features with filters was associated with lower satisfaction, whereas modifying body shape had mixed effects, sometimes improving satisfaction. These findings highlight the dual role of filters as both a tool for self-expression and potential driver of body image distortions. The nuanced impact of filters calls for innovative interventions that not only foster media literacy but also encourage adolescents to critically engage with digital representations of the self, fostering resilience against distorted body ideals.
Keywords: digital filter; body image; social media; mental health; adolescents